Exponential Parsimony to Generate Herd Immunity Against SARS- CoV2 Cybernetically Restricting Doxastic and Desiderative Logics - Lamothe Mara; Lamothe Nery; Lamothe Daniel; Hernández-Garcia Andres; Castillo Crisanto; Alonso-Altamirano Alejandro; Kuri Salim; Clemente-Herrera Adriana; J. Lamothe Pedro (International Journal of Coronaviruses, 2021)
We Hypothesize that It should be intuitively inferred that the behavior of the pandemics corresponds to the prediction of the Maxwell Boltzmann distribution, which is a direct function of population density. In a higher organizational metalevel, it is analogous to the Brownian movement effect, in which the possibility of being observed is determined by the observational power of the instrument. In this case, it corresponds to the sensibility and sensitivity of the probe as well as the prevalence of the arbitrary states. The states are formally considered as a partition in probability theory; both in the Kolmogorov and frequentist approach. All these become subsumed to the Bayes theorem applied to recursive conditional probability.
Keywords: COVID-19